Measuring the Quality of Provider Services with the Service Quality Method at the Public Health Center in Kotamobagu City - Darmin Darmin; Sarman Sarman (Jurnal Ilmu Kesehatan, 2021)
One of the health service facilities that have a very important role in providing health services to the community is the Community Health Center. Assessment of the quality of health services is very important because it can be used as material for self-evaluation of health care provider organizations. assessment of research respondents using a questionnaire consisting of 30 statements. This research is a type of qualitative research, using an observational analytic approach with a questionnaire as a tool in collecting data. The research was conducted at the Kotamobagu City off all Public Health Center in April 2021. The population in this study were all 1000 patients undergoing treatment at the Kotamobagu City Public Health Center, North Sulawesi province. samples in this study as many as 200 patients were determined using a Slovin calculation technique. The sampling technique in this study uses probability simple random sampling. The quality of health services at the Public Health Center in Kotamobagu City is not optimal, it is known that the health services felt by the community are not following what was conveyed by the health service manager at the Kotamobagu City Health Center with a significant level of (α = 0.000 < 0.05). The quality of health services received by the community who utilize services in all Public Health Centers in Kotamobagu City is considered not optimal because the dimension that is lacking in its implementation in public health centers is the dimension of Reliability Responsiveness Assurance Empathy.